Requiem for Universal Jurisdiction in Spain - Esteve Moltó, José (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2020)
The two relevant legislative reforms that universal jurisdiction was subjected to have been a serious blow to the fight against impunity in Spain. The reasons for this de facto repeal of universal justice can only be explained by political interference of foreign governments whose citizens were cornered by Spanish justice. However, with regard to the 2014 reform, there was the possibility that the Constitutional Court might declare that the reform violated some articles of the Spanish Constitution. This last hope evaporated when this court recently rejected the appeals. First, the ruling on 20 December 2018 rejected the Socialist MPs’ arguments. Then, with this precedent, in 2019 the vast majority of cases pursuing international crimes – Tibet, Falun Gong, Rwanda, Guantanamo, the Ashraf refugee camp in Iraq, Couso – were definitively closed. After having exhausted all Spain’s internal options, now the different appeals before the European Court of Human Rights are being rejected. Meanwhile, universal jurisdiction has only survived in the Spanish courts if it involves pursuing a few cases of terrorism, leaving those who were being investigated for war crimes and genocide to go scot-free.